Cardiomyopathies in Tropical Countries: Causes and Nosological Perspective - Touze, Jean-Etienne; Fourcade, Laurent (Scientific Research, 2013)
Background: Cardiomyopathy is the main cause of heart failure in developing countries, mainly in Africa. In those areas the concept of “tropical cardiomyopathy” is still used to design all unexplained cardiomyopathy. The primary aim of this review is first to review the main etiologies of cardiomyopathies observed in tropical countries and second to gain a better understanding of the nosological place of the so-called “tropical cardiomyopathies” in the current framework of cardiomyopathies. Methods and Results: We reviewed relevant references over the last forty years (June, 1976 to May 2012). Given literature data, endomyocardial fibrosis (EMF) is mainly diagnosed in sub-Saharan countries, as well as Brazil and India. Peripartum cardiomyopathy (PPCM) is observed with a higher prevalence than in temperate countries. Sickle cell anemia does not induce specific cardiomyopathy in all echocardiographic studies. Malnutrition and chronic anemia can induce reversible cardiac dysfunction. Myocardial involvement in parasitic infections is restricted to Chagas disease and probably to human African trypanosomiasis. Helminthiasis is not involved in the pathogenesis of cardiomyopathy except for the deleterious effect of high eosinophilia induced by some endemic diseases (filariasis, schistosomiasis). Primary cardiomyopathies (dilated, hypertrophic, and restrictive cardiomyopathy) have no specificity. Arrhythmogenic right ventricular dysplasia and left ventricular noncompaction are also reported and do not differ from elsewhere. Conclusions: The concept of tropical cardiomyopathy is no longer relevant as most of the cardiomyopathies observed in tropical countries have no specificity, with few exceptions (PPCM, EMF, Chagas disease). In this context, the European Society of Cardiology classification offers a simpler clinical approach and allows the inclusion of the rare tropical specificities
Keywords: Tropical Countries; Cardiomyopathy; Endomyocardial Fibrosis; Peripartum Cardiomyopathy; Chagas Disease